Impact of praseodymia additions and firing conditions on structural and electrical transport properties of 5 mol.% yttria partially stabilized zirconia (5YSZ) - Natoli, Alejandro (2021)
Ceramics samples with the nominal composition [(ZrO2)0.95(Y2O3)0.05]1-x[PrOy]x and praseodymia contents of x = 0.05–0.15 were prepared by the direct firing of compacted 5YSZ + PrOy mixtures at 1450–1550 C for 1–9 h and characterized for prospective applicability in reversible solid oxide cells. XRD and SEM/EDS analysis revealed that the dissolution of praseodymium oxide in 5YSZ occurs via the formation of pyrochlore-type Pr2Zr2O7 intermediate. Increasing PrOy additions results in a larger fraction of low-conducting pyrochlore phase and larger porosity, which limit the total electrical conductivity to 2.0–4.6 S/m at 900 C and 0.28–0.68 S/m at 700 C in air. A longer time and higher temperature of firing promotes the phase and microstructural homogenization of the ceramics but with comparatively low effect on density and conductivity. High-temperature processing leads to the prevailing 3+ oxidation state of praseodymium cations in fluorite and pyrochlore structures. The fraction of Pr4+ at 600–1000 C in air is less or equal 2% and is nearly independent of temperature. 5YSZ ceramics with praseodymia additions remain predominantly oxygen ionic conductors, with p-type electronic contribution increasing with Pr content but not exceeding 2% for x = 0.15 at 700–900 C. The average thermal expansion coefficients of prepared ceramics are in the range of 10.4–10.7 ppm/K.